Intraoperative nerve monitoring during thyroid surgery. Issue 5 (October 2016) - Gardner, Ivy H.; Doherty, Gerard M.; McAneny, David
Abstract : Purpose of review: Laryngeal nerve injury, resulting in speech and swallowing dysfunction, is a feared complication of thyroid operations. Routine visualization of the recurrent laryngeal nerve (RLN) has decreased the likelihood of nerve injury, and intraoperative nerve monitoring has been applied in the hope of further enhancing safety. Recent findings: There is conflicting evidence about the value of nerve monitoring during thyroid operations, despite ample research. The data favor nerve monitoring in certain situations, such as neck re-explorations, contralateral RLN injury, extensive or challenging dissections, invasive tumors or large goiters, and nonrecurrent or branching recurrent laryngeal nerves. Continuous intraoperative nerve monitoring may reduce the chances of excessive traction, which is the most common mechanism of injury. Nerve monitoring may also identify and protect the external branches of the superior laryngeal nerve. Summary: Surgeons should routinely identify recurrent laryngeal nerves during thyroid operations, and intraoperative nerve monitoring might be a useful adjunct to prevent injury. As a result of the relatively low probability of permanent recurrent laryngeal nerve injury, it is difficult to establish the absolute value of nerve monitoring. Further research may focus on continuous nerve monitoring and intraoperative monitoring of the external branches of the superior laryngeal nerves.